2019
DOI: 10.1055/s-0039-1698752
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Disorders: Pearls and Pitfalls

Abstract: Dizziness and vertigo are symptoms that commonly lead patients to seek neurologic or emergency care. Because symptoms are often vague and imprecise, a systematic approach is essential. By categorizing vestibular disorders based on the timing, triggers, and duration of symptoms, as well as emphasizing focused ocular motor and vestibular examinations, the majority of vestibular diagnoses can be made at the bedside. This paper will discuss the pearls and pitfalls in the history and examination of the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 127 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…Dizziness can also result from pathologies of the central nervous system, such as concussion, migraine, tumors, and traumatic brain injury ( 244 ). There are over 20 vestibular disorders, and most present with the common symptoms of vertigo, dizziness, oscillopsia, and unsteadiness ( 245 ). One study assessing vestibular disorders and somatization interaction found that Meniere’s disease and vestibular migraines have the highest psychiatric comorbidity ( 246 ).…”
Section: Dizziness Unsteadiness Light-headedness or Faintnessmentioning
confidence: 99%
“…Dizziness can also result from pathologies of the central nervous system, such as concussion, migraine, tumors, and traumatic brain injury ( 244 ). There are over 20 vestibular disorders, and most present with the common symptoms of vertigo, dizziness, oscillopsia, and unsteadiness ( 245 ). One study assessing vestibular disorders and somatization interaction found that Meniere’s disease and vestibular migraines have the highest psychiatric comorbidity ( 246 ).…”
Section: Dizziness Unsteadiness Light-headedness or Faintnessmentioning
confidence: 99%
“…With the expansion of the clinical examination, the vHIT, having good sensitivity and specificity, is crucial in making or supporting the diagnoses of vestibular disorders, such as vestibular neuritis (VN), bilateral vestibular loss, and acoustic neuroma, as well as assessing vestibular compensation during the rehabilitation process ( 3 ).…”
Section: Introductionmentioning
confidence: 99%